2010
DOI: 10.1186/2047-783x-15-4-139
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography discloses identical distribution of liver fibrosis in chronic hepatitis C between HIV-negative and HIV-positive patients on HAART

Abstract: ObjectiveProgressive immunodeficiency associated with HIV-infection leads to a progressive course of liver disease in HIV/HCV-co-infected patients. Highly active antiretroviral therapy (HAART) efficiently restores and preserves immune functions and has recently been demonstrated to also result in reduced liver-related mortality in HIV/HCV-co-infected patients.MethodsTo analyse differences in current liver fibrosis as a possible effect of HAART on fibrosis progression we assessed hepatic fibrosis by transient e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…However, Brau et al has reported slower fibrosis progression in coinfected patients with HAART-associated HIV suppression 21. This is further supported by a recent paper which used transient elastography to suggest that fibrosis rates in HCV/HIV coinfected subjects was now similar that seen in HCV monoinfection 22. Finally, we suspect that there has been a significant evolution in antiretroviral therapy which is reflected in decreased rates of drug-associated hepatoxicity.…”
Section: Discussionsupporting
confidence: 62%
“…However, Brau et al has reported slower fibrosis progression in coinfected patients with HAART-associated HIV suppression 21. This is further supported by a recent paper which used transient elastography to suggest that fibrosis rates in HCV/HIV coinfected subjects was now similar that seen in HCV monoinfection 22. Finally, we suspect that there has been a significant evolution in antiretroviral therapy which is reflected in decreased rates of drug-associated hepatoxicity.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, a cross-sectional comparison between coinfected patients on ART and HCV-monoinfected patients observed no difference in the distribution of liver stiffness [46].…”
Section: Indirect Effects Of Antiretroviral Therapy In Hiv/hepatitis mentioning
confidence: 99%
“…There is evidence to suggest that HIV interacts directly with multiple liver cell types[817]. Furthermore, some studies in adults have shown an association between control of HIV replication and favorable effect on liver fibrosis either by histopathology[18], or by novel approaches such as transient elastography[19], leading to speculation that these findings may be partly explained by interactions between hepatic stellate cells and HIV glycoproteins resulting in stimulation of collagen production[20]. …”
Section: Introductionmentioning
confidence: 99%